Respuesta :

Answer:

(x+1)^2

Step-by-step explanation:

(g ° f) (x) = g(f(x))

g ( f(x)) means that you are going to replace x in g(x) for f(x)

g(x) = x^2

f(x) = x+1

So you have to solve g(x) when x = x+1

g (x+1) = (x+1)^2

Answer:

B) (x+1) ( x²).

Step-by-step explanation:

Given  : f(x)=x+1 and g(x) = x².

To find : what is (g∘f) (x).

Solution : We have given

f(x)=x+1 and g(x) = x².

By the rule :

(g∘f) (x) = g(x) * f(x).

Plugging the values

(g∘f) (x) = (x+1) ( x²).

Therefore, B) (x+1) ( x²).

ACCESS MORE